2016
DOI: 10.5963/ijep0601004
|View full text |Cite
|
Sign up to set email alerts
|

Using Extracellular Enzyme Activity as a Pollutant Indicator: a Field Study in Chinchiná River, Caldas – Colombia

Abstract: The present study investigated the existence of a relationship between Extracellular Enzyme Activity (EEA) of glucosidase and alkaline phosphatase and pollution by carbon and phosphorous at five stations on the Chinchiná River in the water main and the biofilm (epilithon/episammon) during three seasons (rainy, dry and transition). Specific substrates were used as sources: 4-Nitrophenyl-β-D-Glucopyranose as a carbon source and 4-Nitrophenylphosphate as a phosphorus source. The product of catalysis (4-nitropheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this study, no correlation between BA and the activity level of any tested enzyme was observed. A-glucosidases and β-glucosidases, whose activity in aquatic environments is connected with polysaccharide degradation [48], had the lowest levels of hydrolytic activity. This may result from the fact that products of lipid and polypeptide depolymerization are better sources of carbon and energy for bacteria than products of polysaccharide hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no correlation between BA and the activity level of any tested enzyme was observed. A-glucosidases and β-glucosidases, whose activity in aquatic environments is connected with polysaccharide degradation [48], had the lowest levels of hydrolytic activity. This may result from the fact that products of lipid and polypeptide depolymerization are better sources of carbon and energy for bacteria than products of polysaccharide hydrolysis.…”
Section: Discussionmentioning
confidence: 99%